Pengaruh Pertumbuhan Penjualan, Profitabilitas Dan Likuiditas Terhadap Struktur Modal Dengan Ukuran Perusahaan Sebagai Variabel Moderasi Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2022 - Utami Matullesy, Putri; Rambe, Rizki Fillhayati; Indrafana, Iman (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
This research aims to determine the effect of sales growth, profitability and liquidity on capital structure with firm size as a moderating variable. The population in this research consists of manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2022. The sampling technique used is purposive sampling with a sample of 70 companies over 5 years, resulting in 350 samples. The analysis technique employed in this research is Moderated Regression Analysis (MRA). Data collection techniques involve literature review and documentation through the official website of the Indonesia Stock Exchange, www.idx.co.id. The research results indicate that sales growth has no effect on capital structure, while profitability and liquidity have a significant negative impact on capital structure for manufacturing companies listed on the Indonesia Stock Exchange during the 2018-2022 period. Furthermore, the Moderated Regression Analysis (MRA) results show that firm size could not moderate the impact of sales growth, profitability and liquidity on capital structure for manufacturing companies listed on the Indonesia Stock Exchange during the 2018-2022 period.